PENGARUH LOKASI, HARGA DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN SUBISIDI KOTA PANGKALPINANG - Andriano Dwi Mardani; Ahmad Yani; Siti Napisah (LPPM STIE PERTIBA Pangkalpinang, 2020)
This study aims to determine the effect of location, price, and brand image on purchasing decisions of Pangkalpinang City housing. The population in this study were consumers who had bought subsidized houses in Pangkalpinang City. The sample was determined based on a non-probability sampling method, with a quota technique of 120 respondents. The results of this study indicate that the influence of location, price, and brand image affects the decision to purchase subsistence houses in the city of Pangggkalpinang